Les Intoxications Volontaires Par Les Pesticides Dans La Région De Rabat-Salé -Zemmour- Zaer Entre 2008 Et 2014 - Aicha, Detsouli; Zakaria, Abidli; Donia, Kharbouch; Soumaia, Hmimou; Latifa, Amiar; Abdelmajid, Soulaymani; Abdelrhani, Mokhtari; Rachida, Soulaymani- Bencheikh (European Scientific Journal, ESJ, 2018)
The objective of this study is to describe the epidemiological characteristics and the risk factors for voluntary poisoning by pesticides in the Rabat-Salé-Zemmour-Zaer region between 2008 and 2014. This is a retrospective study of cases of voluntary poisoning by pesticides collected between 2008 and 2014 by the Anti-poisoning and Pharmaco-vigilance Center of Morocco. During the study period, 598 cases of voluntary pesticide intoxication were collected. These voluntary intoxications mainly concerned adults whose age is between 20 and 74 years. Female addicts dominated the scene with 61.87% and a sex ratio (F / H) of 2.02 in favor of female sex, with urban predominance. The risk was related to the use of raticides (195 cases). The evolution was favorable in 94% of cases, with 27 people dying during this period.